Clinical Spectrum of Disorders of Sexual Differentiation in Children - Batool, Zarka; Sattar, Hina; Anwar, Haniyah; Saeed, Shayan; Mahmood, Aneela; Mushtaq, Iqra (Biological and Clinical Sciences Research Journal, 2025)
Disorders of sexual differentiation (DSD) are a heterogeneous group of congenital conditions characterized by atypical development of chromosomal, gonadal, or anatomical sex. Objective: To evaluate the clinical spectrum, modes of presentation, and underlying etiologies of DSD in children presenting with ambiguous genitalia. Methods: This cross-sectional study was conducted at the Department of Pediatrics, Rawalpindi Medical University (RMU) and Allied Hospitals from August 2023 to July 2024. A total of 110 children aged from birth to 12 years with ambiguous genitalia were enrolled using non-probability consecutive sampling. Data were collected using a predesigned proforma, including detailed history, physical examination, External Masculinization Score (EMS), and Prader staging for 46 XX cases. Results: The mean age at presentation was 3.8 ± 2.9 years, with 62.7% presenting in infancy. Ambiguous genitalia at birth was the most common mode of presentation (65.5%), followed by inguinal/labial swellings (16.4%). Among 46 XY patients (n=64), androgen insensitivity syndrome (28.1%) and 5-α reductase deficiency (18.8%) were the most frequent causes. In 46 XX patients (n=46), congenital adrenal hyperplasia was predominant (73.9%), with ovotesticular DSD accounting for 17.4%. Most 46 XX patients exhibited moderate to severe virilization (Prader stages III–IV). The mean EMS across all patients was 5.4 ± 2.3, consistent with the presence of genital ambiguity. Conclusion: DSD in children most commonly presents at birth with ambiguous genitalia, with AIS and CAH being the leading etiologies among 46 XY and 46 XX patients, respectively. The high proportion of severe genital ambiguity reflects delays in referral and Diagnosis.